Prevalence of piperacillin-tazobactam induced hypersensitivity reaction in workers of Stallion’s Pharmaceutical factory at Lahore - Anwar Ali Sulehri; Hafiz Muhammad Hammad Yaqub; Humayun Suqrat Hassan Imam; Uzma Sagheer; Muhammad Abubakar (Journal of University Medical & Dental College, 2022)
BACKGROUND & OBJECTIVE: Piperacillin is an antibiotic that belongs to the ureidopenicillin family. Piperacillin-tazobactam provides cover against gram-positive, gram-negative bacteria and some bacteria of anaerobic nature. It is an extended-spectrum antibiotic and is used along with tazobactam which is an inhibitor of beta-lactamase. The main objective of our research was to identify the hypersensitivity reactions of piperacillin-tazobactam in pharmaceuticals factory and office workers. METHODOLOGY: A Cross-sectional study was conducted at Stallion Pharmaceuticals (Pvt) Ltd located at Sundar Industrial Estate Lahore, Pakistan, from March to April 2018, after approval from the institutional research committee. All the workers, including factory workers and office workers at Stallion Pharmaceuticals (Pvt) Ltd were included in this study. Data was collected from each respondent by immediate-type skin testing. Data analysis was done by SPSS version 25, the demographic data was evaluated by descriptive statistics, Fisher Exact test was used for comparison and p≤0.05 was taken as significant. RESULTS: The results of the study presented that hypersensitivity reaction was present in (7.5%) of males and (3.8%) of females. It was also observed that (8.8%) of factory workers had hypersensitivity reactions when they are gone through skin tests, and only (2.5%) of office workers were skin test positive. From the above results (11.2%) of all the respondents developed hypersensitivity reactions and (88.8%) showed no reaction when they were gone through skin tests, which contain 0.1 ml of piperacillin and tazobactam. Fisher exact test was applied, and results showed no significant difference between hypersensitivity reactions among factory and office workers as the p-value was 01. CONCLUSION: Hypersensitivity reaction to piperacillin-tazobactam was minimal in the factory & office workers, and this was not significant.